The fourth world: an indigenous perspective on feminism and aboriginal women's activism - Ouellette, Grace Josephine Mildred Wuttunee (Fernwood Publishing, 2002)
"This book is not about feminism. Rather, feminism is the basis of the discussion, an example of how understanding oppression must consider a number of barriers. Euro-Canadian feminists rarely address the circumstances that are unique to First Nations' women, instead working with the assumption that all women are a part of a similar struggle. Ouellette attempts to confront these barriers. Throughout interviews with a number of women, she highlights the following four questions. To what extent do Aboriginal women understand experience and articulate their oppression? To what extent do colonized women perceive racism as the source of their oppression? To what extent do Aboriginal women view male domination within their own Aboriginal societies as the source of the oppression? How do Aboriginal women articulate racism and gender oppression?The author argues that there will always be a dichotomy between European and Aboriginal thought. This book makes an important contribution toward a greater understanding of Aboriginal thought and an Aboriginal perspective on society. The Fourth World theory is an integrate part of the "Circle of Life" philosophy of Aboriginal people. In keeping with oral traditions, these teachings are passed on at gatherings and in private conversations. They compromise a distinctly Aboriginal worldview."
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; études autochtones

La violence nazie, une généalogie européenne - Traverso, Enzo (La Fabrique, 2002)
La violence nazie ne doit rien au hasard: elle a une généalogie, qui n'est pas spécifiquement allemande, et un laboratoire, l'Europe libérale du XIXe siècle.Les camps d'extermination sont l'aboutissement d'un long processus de déshumanisation et d'industrialisation de la mort, amorcé par la guillotine et qui a progressivement intégré la rationalité du monde moderne, celle de l'usine, de la bureaucratie, de la prison. On peut trouver les origines culturelles du nazisme dans le "racisme de classe" qui triomphe après la Commune, dans le discours impérialiste sur l'"extinction des races inférieures" visant à légitimer les génocides coloniaux, enfin dans l'émergence d'une nouvelle image du juif- axée sur la figure de l'intellectuel - comme métaphore d'une maladie du corps social.Le nazisme réalisera la convergence entre ces différentes sources matérielles et idéologiques. Auschwitz se révèle ainsi - et c'est là que réside, selon Enzo Traverso, sa singularité - comme la synthèse d'un ensemble de modes de pensée, de domination et d'extermination profondément inscrits dans l'histoire occidentale.
disponible en ligne : https://shs-cairn-info.proxy.bibliotheques.uqam.ca/la-violence-nazie–9782913372146?lang=fr donné en lecture au cours POL5480, p.44-91.
Keywords: 1900-1999; 1930-1939; 1940-1949; allemagne; approches et analyses; cours; discipline; europe; histoire; histoire et politique; pol5480; premier cycle; périodes historiques; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences